1994
DOI: 10.1136/bjo.78.8.643
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the lamina cribrosa by elevated intraocular pressure.

Abstract: The purpose ofthis study was to determine the mechanical response of the lamina cribrosa (LC) to elevated intraocular pressure (IOP) so as to identify possible mechanisms of optic nerve damage in early glaucoma. Ten In this paper, we seek to complement previous work by a direct morphometric study of the response of the LC in normal human eyes to acute changes in IOP. We feel that this approach has several advantages. Firstly, a morphometric approach allows both the overall shape and the internal architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
153
2
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(174 citation statements)
references
References 12 publications
12
153
2
2
Order By: Relevance
“…This may induce changes in load-bearing connective tissues that results in laminar thinning, peripapillary scleral bowing posteriorly, and expansion of the scleral canal. 4,[25][26][27][28][29][30] Our findings in humans are consistent with experimental studies in dogs. Using confocal scanning laser tomography, 31,32 has shown that intracranial hypertension displaces the optic disc surface and lamina cribosa anteriorly (toward the vitreous), whereas ocular hypertension displaces the disc surface posteriorly.…”
Section: Discussionsupporting
confidence: 81%
“…This may induce changes in load-bearing connective tissues that results in laminar thinning, peripapillary scleral bowing posteriorly, and expansion of the scleral canal. 4,[25][26][27][28][29][30] Our findings in humans are consistent with experimental studies in dogs. Using confocal scanning laser tomography, 31,32 has shown that intracranial hypertension displaces the optic disc surface and lamina cribosa anteriorly (toward the vitreous), whereas ocular hypertension displaces the disc surface posteriorly.…”
Section: Discussionsupporting
confidence: 81%
“…We assumed as clinically relevant the changes occurring between moderate and severe glaucoma cases, 15 and we therefore estimated D (the difference between post-and preinterventional RNFL) at 20 microns and s at 40 microns (20). The following formula for continuous, paired data were used:…”
Section: Statistical Issuesmentioning
confidence: 99%
“…They postulated that when IOP was reduced after glaucoma filtering surgery, anterior repositioning of posteriorly displaced lamina cribrosa and simultaneous reformation of neuroretinal tissue would occur. 19,20 Cup shape is a description of the distribution of depth values. Cups with gradually sloping borders tend to have more negative values, and cups with steep sloping walls tend to have less negative or even positive values.…”
Section: Short-term Changes After Trabeculectomy M Figus Et Almentioning
confidence: 99%
“…Elevated intraocular pressure (IOP) typically accompanies glaucoma. Elevated IOP leads to regions of high shear stress and strain in the lamina cribrosa, the region of the eye where the optic nerve traverses the globe (Zeimer & Chen, 1987;Cahane & Bartov, 1992;Fechtner & Weinreb, 1994;Yan et al 1994). Retinal ganglion cells, which make up the optic nerve, undergo apoptosis upon exposure to elevated IOP in rat (Brubaker, 1996) and rabbit (Quigley et al 1995) models of glaucoma.…”
mentioning
confidence: 99%